Why Dieters Succeed or Fail: The Relationship Between Reward and Punishment Sensitivity and Restrained Eating and Dieting Success - Jonker, Nienke C.; Bennik, Elise C.; de Jong, Peter J. (Frontiers in Psychology, 2021)
Background: The current study set out to improve our understanding of the characteristics of individuals who are motivated to restrict their food intake yet who nevertheless fail to do so. We examined whether punishment sensitivity (PS) was related to restrained eating, and reward sensitivity (RS) to perceived dieting success. Additionally, it was examined whether executive control moderates the association between RS and perceived dieting success. Methods: Female student participants (N = 290, aged 17-29, BMI between 18.5-38.0) completed questionnaires on restrained eating, perceived dieting success, RS and PS, and carried out a behavioral task to index executive control. Results: PS was indeed positively related to restrained eating. RS was positively related to perceived dieting success, yet, executive control did not moderate this association. Conclusion: The current study adds to the evidence that PS is related to individuals’ motivation to restrict their food intake. Furthermore, it shows support for the suggestion that RS may facilitate food restriction.